Prognosis of women with primary breast cancer diagnosed during pregnancy: results from an international collaborative study - Amant, Frédéric; von Minckwitz, Gunter; Han, Sileny N; Bontenbal, Marijke; Ring, Alistair E; Giermek, Jerzy; Wildiers, Hans; Fehm, Tanja; Linn, Sabine C; Schlehe, Bettina; Neven, Patrick; Westenend, Pieter J; et al. (Journal of clinical oncology, 2013)
We aimed to determine the prognosis of patients with breast cancer diagnosed during pregnancy (BCP). In this cohort study, a multicentric registry of patients with BCP (from Cancer in Pregnancy, Leuven, Belgium, and GBG 29/BIG 02-03) compiled pro- and retrospectively between 2003 and 2011 was compared with patients who did not have associated pregnancies, using an age limit of 45 years. Patients with a diagnosis postpartum were excluded. The main analysis was performed using Cox proportional hazards regression of disease-free survival (DFS) and overall survival (OS) on exposure (pregnant or not), adjusting for age, stage, grade, hormone receptor status, human epidermal growth factor 2 status, histology, type of chemotherapy, use of trastuzumab, radiotherapy, and hormone therapy. The registry contained 447 women with BCP, mainly originating from Germany and Belgium, of whom 311 (69.6%) were eligible for analysis. The nonpregnant group consisted of 865 women. Median age was 33 years for the pregnant and 41 years for the nonpregnant patients. Median follow-up was 61 months. The hazard ratio of pregnancy was 1.34 (95% CI, 0.93 to 1.91; P = .14) for DFS and 1.19 (95% CI, 0.73 to 1.93; P = .51) for OS. Cox regression estimated that the 5-year DFS rate for pregnant patients would have increased from 65% to 71% if these patients had not been pregnant. Likewise, the 5-year OS rate would have increased from 78% to 81%. The results show similar OS for patients diagnosed with BCP compared with nonpregnant patients. This information is important when patients are counseled and supports the option to start treatment with continuation of pregnancy.